Choline and Folic Acid Balance in Diets During Pregnancy Programs Food Intake Regulation in Wistar Rat Offspring (FS08-05-19). (13th June 2019) - Hammoud, Rola; Liao, Chih-Sheng; Pannia, Emanuela; Ho, Mandy; Yang, Neil; Kubant, Ruslan; Chatterjee, Diptendu; Arning, Erland; Bottiglieri, Teodoro; Pausova, Zdenka; Anderson, G Harvey
Abstract: Objectives: High gestational folic acid (FA) induces an obesogenic phenotype in male Wistar rat offspring. Imbalances between FA and other methyl-nutrients (i.e., choline) leading to perturbations in the 1-carbon cycle may account for the effects of high FA diets. Canadian women consume high (2–7-fold) intakes of FA, but most are not meeting recommended adequate intakes for choline. Choline is also absent from Canadian prenatal supplements. The objective of this study is to evaluate the effects of the interaction between choline and FA in maternal diets of rats on the 1-carbon cycle, and the programming of food intake, body weight gain and biomarkers of obesity in the offspring later in life. Methods: Pregnant Wistar rat dams were fed the AIN-93 G diet with recommended (1X) choline and FA (RCRF, control), or a 5X FA diet with either 0.5X choline (LCHF), 1X choline (RCHF), or 2.5X choline (HCHF). Brain and blood were collected at birth. At weaning one male pup/dam from all groups was maintained on the control diet for 20 weeks then terminated. Dependent measures include weekly body weight-gain and food intake, plasma glucoregulatory hormones and 1-carbon metabolites at birth and post-weaning. Results: Increasing choline content to 2.5-fold in a high (5-fold) gestational FA diet (HCHF) led to lower plasma insulin and leptin levels at birth compared to the LCHF and RCHF diets, respectively ( P  < 0.05). It also led to lower (25%, P  = 0.03) plasma 5-methyltetrahydrofolate concentrations at birth compared to the RCHF diet, suggesting more efficient utilization of FA. Offspring born to dams maintained on a high folic acid diet with either low or recommended choline had higher weekly food intake (6%, P  < 0.05) and body weight-gain (9%, P  < 0.01). In contrast, offspring from dams fed the HCHF gestational diet were not different from those born to dams fed the RCRF (control) diet, highlighting the mitigating effects of a balanced choline and FA gestational diet. Conclusions: Increased intakes of choline mitigate the effects of high FA diets. Maternal dietary choline interacts with FA on the long-term programming of food intake regulation in the offspring; emphasizing a need for more attention to improving choline intakes by women of child-bearing age. Funding Sources: This research was funded by the Canadian Institute of Health Research, Institute of Nutrition, Metabolism and Diabetes (CIHR-INMD).